Dietary patterns in cardiovascular diseases prevention and management - Dimassi, Hani (2014)
The objective of this paper is to discuss the advantages of using the dietary pattern approach in evaluating the role of diet in cardiovascular diseases (CVD) prevention and management and to report on the association between major dietary patterns and CVD risk factors among Lebanese adults. The significance of this type of research to primary care physicians is also highlighted. The dietary pattern approach overcomes the inconsistent findings of single nutrient analysis in evaluating diet-disease associations, takes into consideration the synergistic effects of nutrients, and provides culture specific recommendations. Using data from the national Nutrition and Non-Communicable Disease Risk Factor Survey, we appraised the association of dietary patterns with CVD risk factors among Lebanese adults. Two major dietary patterns were identified: Western pattern, characterized by high intake of fast food sandwiches, desserts, and carbonated beverages and the traditional Lebanese pattern, characterized by high intakes of fruits and vegetables, olives and olive oil, and traditional dishes. Only the Western pattern was associated with increased risk of obesity (abdominal obesity), hyperglycemia and the metabolic syndrome. These findings demonstrated the valuable results that can be obtained using the dietary patterns approach in evaluating the association between diet and CVD risk factors and provided evidence that this approach can be used as a tool to push for desirable dietary changes in the country.